Improving the performance of public service organisations: building capabilities to recover and renew - Seabra, Sérgio Nogueira (My University, 2010)
Over the past 20 years, governments in many countries around the world have sought to implement governance mechanisms to measure and assess the performance of public service organisations. As a consequence, public service organisations, especially those considered as poorly-performing organisations, have been subjected to unprecedented pressure to improve their performance and sustain performance improvement as a continuous process. However, efforts of public managers to improve the performance of their organisations have been undertaken without “comprehensive theories and rigorous evidence on this issue” (Boyne, 2006: 366). This thesis takes up the challenge of providing robust evidence on the factors associated with the performance improvement of public organisations. We propose that the notion of organisational capabilities offers a promising way to meet this challenge. From this standpoint, this research sought to identify the organisational capabilities whose development and use explain a public service organisation’s ability to improve its performance and sustain good performance in the long run. The empirical analysis was conducted in a population of hospital trusts in England. We firstly applied longitudinal and comparative case studies method into two acute hospitals trusts: one case of a successful performance improvement and one case of less-successful performance improvement. The purpose was to examine how the development (or lack of) a set of capabilities over time accounted for the differences in the performance outcome and trajectory of the two cases. Our findings identified the following capabilities as advantageous for achieving a sustained performance: collective leadership; action-oriented culture; effective clinical-managerial relationship; supportive external context; performance/finance control capability; coordination capability of the key delivery process; sensing capability and learning capability. We then employed quantitative method over the population of acute hospital trusts in England to explore the relationship between complementarities of capabilities and performance. The results demonstrated that only when in combination does the presence of the capabilities yield positive and significant association with performance. In other words, the presence of the whole system of the capabilities increases the trusts’ performance, while partial presence of a set of capabilities is either not significantly associated with, or even detrimental to, the trusts’ performance.
Keywords: Transparência Pública; UNIDADE::SECRETARIA-EXECUTIVA (SE)::DIRETORIA DE GESTÃO INTERNA (DGI)::Coordenação-Geral de Gestão de Pessoas (COGEP); Performance of public service organisations; Improvement; VCCGU::Prevenção da Corrupção, Integridade e Transparência Pública